UNEMPLOYMENT AND ITS DETERMINANTS - Saidov Khabibulla Shavkat ogli (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
One of the major macroeconomic indicators of the country, which essence signifies the vital aspect of the whole population, is unemployment. It poses significant challenges for all countries since employment stands as one of the key determinants for economic growth. To be precise, employment provides the means for living for all people to sustain not only their social but economic and political well-being as well. Therefore, it is a subject of great importance for states to maintain low unemployment rates, and those of the great authority should contribute to the establishment of policies regarding the development of the unemployment indicator.